TOWARD AN INCLUSIVE PAPUA: HARMONIZATION OF INDIGENOUS LEGAL VALUES AND GENDER EQUALITY PRINCIPLES IN WOMEN’S EMPOWERMENT - Heru Andryana Suherman; Fadillah Wulansari; Bambang Heryanto; Hera Fauziah Lubis (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
Papua, a region rich in cultural heritage and indigenous legal systems, faces persistent challenges in achieving gender equality and empowering women. Despite their significant contributions to socio-economic life, particularly in agriculture, natural resource management, and local trade, Papuan women remain marginalized within customary decision-making structures and formal political institutions. This study explores the intersection of indigenous legal values and gender equality principles in Papua, focusing on the need for legal harmonization to promote women’s empowerment. Gender inequality in Papua is rooted in entrenched patriarchal values that place women in subordinate roles, limiting their access to education, economic resources, and decision-making opportunities. Legal pluralism, where customary law coexists with national laws, often reflects conflicting norms that hinder women’s rights and participation. The research advocates for a dialogical, participatory approach to legal reform, where customary values are interpreted in ways that support gender equality, without undermining local wisdom. Empowerment strategies, including legal education, economic development programs, and policy reforms, are essential to ensure that Papuan women can actively participate in societal transformation. The study emphasizes the importance of inclusive policy-making, gender-sensitive legal frameworks, and community involvement in achieving sustainable development and social justice. By integrating gender equality principles into Papua’s legal systems, both customary and state law, the region can move towards a more inclusive and just society. Women’s empowerment is not only crucial for gender justice but also serves as a key driver of economic growth and sustainable development. This study ultimately calls for a comprehensive approach to harmonizing indigenous legal systems with national principles of gender equality, ensuring that Papuan women are not only recognized for their contributions but also given the opportunity to shape their futures.